Entretiens en autoconfrontation croisée : une méthode en clinique de l’activité - Yves Clot; Daniel Faïta; Gabriel Fernandez; Livia Scheller (Perspectives Interdisciplinaires sur le Travail et la Santé)
The paper presents a co-analysis methodology that we call a crossed self-confrontation. It involves distinguishing between work done and "real" work, and aims to identify the activity’s potential or prevented developments, in order to eventually transform their course. An initial phase involves co-design of the work environment, and is followed by a second phase of video recordings of what the operators do, what they say about it, and lastly, what they do about what they said. Using variants of the professional genre, each operator analyzes the style of his or her actions. Confronted binomially with their activity, they then become involved in professional controversies concerning the genres based on the styles of their actions. The crossed self-confrontation methodology, inseparable from an activity clinic, also aims to renew the analysis of work. This type of analysis allows us to approach health as the subject’s power to act on his or her environment and self.